Pengembangan Potensi Pusat Kota Serang sebagai Wisata Heritage Perkotaan Berbasis Masyarakat - Sahabudin, Arfah; Rusdin, Rusdin; Hadian, M. Sapari Dwi (Jurnal Master Pariwisata (JUMPA); Volume 07, Nomor 01, Juli 2020DO - 10.24843/JUMPA.2020.v07.i01.p07, 2020)
The existence of the potential for heritage tourism in center of Kota Serang is now almost eliminated and forgotten, whereas if it is managed optimally, many benefits can be generated. The purpose of the research is to reveal the potential of heritage tourism in center of Kota Serang to be developed as a tourist destination. The research method used is a qualitative method. Primary data collection through observation techniques and in-depth interviews. Secondary data through library research. Data analysis uses an interactive model, through three activities namely data reduction, data presentation, and drawing conclusions. The results of the study indicate that there is no clear strategic policy and the lack of efforts in achieving optimal utilization of potential inheritance for tourism development. The synergy of all stakeholders and decision makers is needed to run in line with the vision and mission of development. The proposed development model is community-based heritage tourism. Keywords: heritage tourism, urban-community-based tourism, urban tourism